THE ROLE OF VALUE ANALYSIS TECHNOLOGY IN REDUCING PRODUCT COSTS-AN APPLIED STUDY AT THE DIWANIYAH TIRE FACTORY - Baqer abdulrahman ali alzameli; Anmar rasool shaieth (Scholar Express Journals, 2025)
This research aims to apply value analysis technology to a public rubber industry company, the Diwaniyah Tire Factory, as it is considered one of the most important strategic cost management techniques in the field of cost accounting and management accounting. To achieve the research objectives, the researcher relied on data from the Diwaniyah Tire Factory through personal interviews with factory employees to apply value analysis technology. The research concluded that eliminating waste and loss in all production processes, as well as processes that do not add value, is essential for reducing product costs. The research concluded with the consideration of transitioning to modern systems and technologies due to the diversity of customer needs and desires and the changing benefits and forms of products
Keywords: Value proposition analysis technique; product cost reduction; transitioning